Archival Studies F The Muslim World İn The Medieval Age: An Evaluation Archival Studies And Archival Structure İn The Period Of Fatimid - M. Hanefi Kutluoğlu; İshak Keskin (Türk Kütüphaneciliği)
Studies on the subject of archival history in Turkey are mainly concentrated on the bureaucratical structures of the investigated periods. The unexistance of enough archival materials and studies on the archival application of this periods has forced the researchers to undertake this type of studies. In case of availability of archival materials, understanding and evaluation of the creation and the preparation of the documents could be easier. The aim of this article is to present an important book on the bureaucratical tradition and archival structure of Fatimid period to the readers. This book also gives some crucial information on historical development of archival studies in The IslamicWorld under theoretical and methodological bases.